The Effect of Wheat Mixtures on the Powdery Mildew Disease and Some Yield Components - Ning LI; Shao-feng JIA; Xiu-na WANG; Xia-yu DUAN; Yi-lin ZHOU; Zong-hua WANG; Guo-dong LU (Journal of Integrative Agriculture)
Mixtures composed of five wheat cultivars, Jingshuang 16, Jing 411, Jingdong 8, Lunxuan 987, and Baofeng 104, with different levels of resistance against powdery mildew were tested for their potential containment of the disease development in the field and for the influence on grain yield and the content of crude protein in the years 2007 and 2010. The plots were inoculated artificially with mixed isolates collected in the fields and propagated in the greenhouse and the disease was scored in 7 d interval during the two growing seasons. It was indicated that certain combinations, e.g., Jingdong 8: Lunxuan 987, Jingdong 8: Baofeng 104, and Jing 411: Jingdong 8: Baofeng 104, showed positive efficacy on the mildew. The cultivar combinations tested in 2007 showed increase of grain yield, while most of the combinations tested in 2010 did not show the increase. The differences of the increases or decreases were not statistically significant except combinations Jing 411: Jingdong 8: Baofeng104, Jingshuang16: Jingdong8: Lunxuang 987 and Jingshuang 16: Jingdong 8: Lunxuan 987: Baofeng 104, which showed the decrease of the grain yield. The mixtures did not show influence on the content of crude protein in grain. More cultivar combinations need to be tested.